IMPLEMENTASI KEBIJAKAN KETAHANAN PANGAN DAN GIZI KABUPATEN KEPULAUAN MERANTI (Studi Kasus Penganekaragaman Pangan dan Perbaikan Gizi Masyarakat Tahun 2019) - Hidayatika "; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In order to ensure the availability of food for the community, the Regional Government of the Meranti Islands Regency through the Food Security, Food Crops and Animal Husbandry Service of the Meranti Islands Regency implements the 2019 Food Diversification and Community Nutrition Improvement policy. The purpose of the research carried out is to describe the implementation of the Food Security and Nutrition Policy in Meranti Islands Regency in an effort to diversify food and improve public nutrition in 2019. The research method used is qualitative research. This type of research is descriptive qualitative. In data collection the writer uses interview and documentation techniques. The results of the study indicate that the implementation of the Food Security and Nutrition Policy in the Meranti Islands Regency in the efforts of Food Diversification and Community Nutrition Improvement in 2019 has not been well implemented. The inadequate implementation of the policy is due to the low intensity of policy program implementation in terms of quantity and quality and has not been able to reach the majority of the people of the Meranti Islands Regency. The response of the Regional Government of the Meranti Islands Regency and the people of the Meranti Islands Regency in responding to the Food Security and Nutrition policy in the Meranti Islands Regency in the 2019 Food Diversification and Community Nutrition Improvement policy has not provided a good response to the implementation of these activities. The Regional Government of the Kepulauan Meranti Regency prioritizes the allocation of funding in the regional infrastructure development sector. Socialization of Food Diversification and Community Nutrition Improvement has not been carried out continuously, because of the limited infrastructure and human resources that handle food and nutrition and the lack of funding budget channeled by the Regional Government of the Meranti Islands Regency towards the implementation of this policy.  Keywords: Policy Implementation, Food Security and Nutrition